Evaluation of an oscillating‐rotating toothbrush with micro‐vibrations versus a sonic toothbrush for the reduction of plaque and gingivitis: results from a randomized controlled trial. (3rd April 2020) - Adam, Ralf; Ram Goyal, C.; Qaqish, Jimmy; Grender, Julie
Abstract : Purpose: To compare a novel oscillating‐rotating (O‐R) electric rechargeable toothbrush with micro‐vibrations to a marketed premium sonic toothbrush for reduction of gingivitis and plaque in an 8‐week randomized controlled trial. Methods: Adult subjects with evidence of gingivitis and plaque were randomized to use either the novel O‐R brush (Oral‐B iO) or the sonic brush with sodium fluoride dentifrice twice daily. Assessments at baseline and week 8 included the Rustogi Modification of the Navy Plaque Index (RMNPI), Modified Gingival Index (MGI), and Gingival Bleeding Index (GBI). Gingivitis status ('healthy'/'not healthy') was classified per the American Academy of Periodontology/European Federation of Periodontology criteria. Results: Ninety subjects were randomized to treatment and completed the study. Subjects had a mean age of 49.2 years; 68 were females. At baseline, the mean number (standard deviation [SD]) of bleeding sites for all subjects was 32.8 (16.43). At week 8, the O‐R brush group had a higher percentage of 'healthy' gingiva subjects than the sonic brush group (84% vs. 53% P  = 0.003). In the between‐group comparisons at week 8, the O‐R brush group showed statistically significantly greater reductions ( P  < 0.001) compared to the sonic group for MGI, GBI, and number of bleeding sites. The O‐R brush group also had statistically significantly greater plaque removal ( P  ≤ 0.011) than the sonic brush group for whole mouth plaque as well as plaque in the proximal regions and along the gingival margin. Conclusions: The novel O‐R electric toothbrush with micro‐vibrations provided greater plaque and gingivitis reductions than the marketed premium sonic toothbrush over 8 weeks.